Adult Aortotracheal Fistula as Sequela of Double Aortic Arch Repair in Infancy: A Case Report. (July 2020) - Rees, Andrew B.; Rodney, Jennifer P.; Gilbert, Mark R.; Kaiser, Clayton A.; Gelbard, Alexander H.
Introduction: Double aortic arch is a rare congenital malformation of the aortic arch that most frequently presents in childhood. Early surgical intervention typically yields excellent outcomes. Objectives: To describe aortotracheal fistula as a rare, yet serious complication of vascular ring and subsequent aortic aneurysm in an adult patient. Methods: Clinical history, as well as radiographic and endoscopic imaging were obtained to describe the development, diagnosis, and clinical course of this patient's aortotracheal fistula. Additionally, follow up data was obtained to document the healing of this fistula after surgical repair. Results: We describe a case of a 46-year-old male with DiGeorge Syndrome and a double aortic arch, repaired in childhood, which developed into an aortotracheal fistula after tracheostomy placement as an adult. Conclusions: This case demonstrates that dangerous complications of a double aortic arch can persist into adulthood, even after surgical repair in infancy. Each patient's unique anatomy must be considered when thinking about airway management and prevention of complications of this rare congenital anomaly.